Anaerobic digestion of paddy husk and dried coconut leaves: a pathway to renewable energy / Rafidah Selaman, Alexandra Dudy Cleareance Anak Gaup and Nurfatin Jaafar - Selaman, Rafidah; Gaup, Alexandra Dudy Cleareance; Jaafar, Nurfatin (Universiti Teknologi MARA, Sabah, 2024)
Recent research has focused on anaerobic digestion (AD) for resource recovery from waste. AD generates biogas, primarily methane, which can be used as a renewable energy source for electricity and heat. This study examines the physical properties and biogas production of paddy husk (PHU) and dried coconut leaves (DCL) through anaerobic mono and co-digestion techniques. Standard methods were used to measure the physical characteristics of both wastes, which included total solids (TS), volatile solids (VS), and pH. The biogas production experiments were conducted in Duran bottles at a mesophilic temperature range of 26°C - 32°C with a set inoculum-to-sample ratio. Biogas production was measured using the water displacement method, with daily records taken over ten days. The TS values for PHU and DCL were 5.08% (± 0.05) and 93.21% (± 0.04), respectively. While the VS values for PHU and DCL were 75.80% (± 0.05) and 91.29% (± 0.07), respectively. This finding shows the suitability of both substrates to undergo the AD process. The pH value shows both wastes in an alkaline state. Results for biogas recovery found that co-digestion between PHU and DCL recovered the highest amount of biogas with 858.0 mL (±0.05), and the optimum time for digestion was on day 9. Meanwhile, single digestion of PHU and DCL recovered biogas with 187.0 mL (±0.12) (Day 8) and 197.0 mL (±0.05) (Day 8), respectively. The findings reveal significant biogas production potential from both PHU and DCL, with mixing digestion yielding higher biogas output and greater process stability. Mixing digestion enhanced the AD process by increasing biogas production and achieving a more balanced nutritional profile. This study provides insights into optimizing AD systems for renewable energy production and sustainable waste managements.